2013
DOI: 10.2494/photopolymer.26.479
|View full text |Cite
|
Sign up to set email alerts
|

Study of Swelling Behavior in ArF Resist during Development by the QCM Method (3) - Observations of Swelling Layer Elastic Modulus -

Abstract: The QCM method allows measurements of impedance, an index of swelling layer viscosity in a photoresist during development. While impedance is sometimes used as a qualitative index of change in the viscosity of the swelling layer, it has not so far been used quantitatively, for data analysis. We explored a method for converting impedance values to elastic modulus (Pa) and a coefficient expressing viscosity. Applying this method, we compared changes in the viscosity of the swelling layer in an ArF resist generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In addition to the initial acid yield, there are other factors that can affect CAR sensitivity, such as acid diffusion and deprotection 116503-3 © 2023 The Japan Society of Applied Physics during PEB. 36,[42][43][44][45][46] The factors behind the higher sensitivity of P1 will be discussed later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the initial acid yield, there are other factors that can affect CAR sensitivity, such as acid diffusion and deprotection 116503-3 © 2023 The Japan Society of Applied Physics during PEB. 36,[42][43][44][45][46] The factors behind the higher sensitivity of P1 will be discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the dissolution properties of polymers in developer solutions have been studied extensively. Thus far, the dissolution properties of KrF, 43,46) ArF, [46][47][48] EB resists, 49,50) and EUV resists and model polymers [51][52][53][54][55][56][57][58] during development have been studied with the advancement of lithographic technology. The resist sensitivity can be determined from whether the initial film elutes into the developer or remains undissolved in the development process when the exposure dose is changed.…”
Section: Resultsmentioning
confidence: 99%
“…The PHS solution was dropped onto the QCM substrate, spin-coated, and prebaked at 90 °C for 90 s. The coated film was developed in a strong basic aqueous developer, and the dissolution dynamics were measured using a QCM-based development analyzer (Litho Tech Japan RDAQz3). 21) After measurement, the film was rinsed with distilled water. Film thickness before and after development was measured with an ellipsometer (Meiwafosis FS-1).…”
Section: Methodsmentioning
confidence: 99%
“…Not only the study described above but also other studies have attempted to describe the relationship between physical properties and observed impedance values quantitatively. [21][22][23][24] However, note that it is difficult to quantitatively explain changes in a heterogeneous material consisting of multiple layers such as a film during development. Hence, we used impedance changes as a qualitative indicator in this study.…”
Section: Quartz Crystal Microbalance Methodsmentioning
confidence: 99%